Somali and the forest spirit. 2 - Gureishi, Yako (Titan Comics, 2025)
Somali and The Golem continue to explore the witch's workshop to learn more about the different types of magic in the world they inhabit. But deep in the labyrinth lies a tome that foretells of a time when humans ruled the world, when humans had been the apex, and where the remaining humans may be. The search for sanctuary begins here!